COVID-19 Lockdown Landslides: The negative impact of subsequent lockdowns on loneliness, wellbeing, and mental health of Australians - Kim Johnston; Jessica Oliva (ACHSM, 2021)
Objective. We previously reported on loneliness, depression, anxiety and stress of Australians living alone during the first COVID-19-related government enforced lockdown in Australia. At this time, those living alone were experiencing relatively low levels of emotional distress. Since then, one state, Victoria, underwent a second extended lockdown period and until now, it was unclear what impact this sequential lockdown might have had on the mental health and wellbeing of Victorian citizens. The current study aimed to add to the emerging literature on the lockdown experience in Australia by directly comparing the levels of anxiety, depression, stress, loneliness, and wellbeing between Victorians in the second extended lockdown and Australians in the first lockdown. Design. Data from our original study of 384 Australians was compared with cross-sectional surveys of 340 Victorians during the second lockdown period. Setting. An online survey was administered with people residing in Victoria self-selecting to complete the study. Outcome Measures. Participants were asked to complete the Depression, Anxiety and Stress Scale (DASS-21), WHO-5 Wellbeing Scale, and the University of California Los Angeles (UCLA) Loneliness Scale. They were also invited to offer their insights into how the second extended lockdown experience had differed from the first. Results. Independent samples t-tests revealed that Australians were significantly more depressed, anxious, stressed, and lonely, and experienced reduced psychological wellbeing in the second lockdown compared to the first however overall, the levels indicated mild psychological distress. Qualitative insights revealed impact on mental health and a feeling of increased restrictions during lockdown two. Conclusions. Participants demonstrated adaptation to the lockdowns, providing support for the measures the Australian government have adopted to physically protect Australians from COVID-19. Management of the negative psychological impact through attention to wellbeing practices is however recommended in light of the increase in mental health concerns and likely further lockdown periods.